Cardiometabolic risk indicators that distinguish adults with psychosis from the general population, by age and gender. - Debra L Foley (Public Library of Science (PLoS), 2013)
Individuals with psychosis are more likely than the general community to develop obesity and to die prematurely from heart disease. Interventions to improve cardiovascular outcomes are best targeted at the earliest indicators of risk, at the age they first emerge. We investigated which cardiometabolic risk indicators distinguished those with psychosis from the general population, by age by gender, and whether obesity explained the pattern of observed differences. Data was analyzed from an epidemiologically representative sample of 1,642 Australians with psychosis aged 18-64 years and a national comparator sample of 8,866 controls aged 25-64 years from the general population. Cubic b-splines were used to compare cross sectional age trends by gender for mean waist circumference, body mass index [BMI], blood pressure, fasting blood glucose, triglycerides, LDL, HDL, and total cholesterol in our psychosis and control samples. At age 25 individuals with psychosis had a significantly higher mean BMI, waist circumference, triglycerides, glucose [women only], and diastolic blood pressure and significantly lower HDL-cholesterol than controls. With the exception of triglycerides at age 60+ in men, and glucose in women at various ages, these differences were present at every age. Differences in BMI and waist circumference between samples, although dramatic, could not explain all differences in diastolic blood pressure, HDL-cholesterol or triglycerides but did explain differences in glucose. Psychosis has the hallmarks of insulin resistance by at least age 25. The entire syndrome, not just weight, should be a focus of intervention to reduce mortality from cardiovascular disease.